SURVEY FOR THE DISEASE STATUS INTENSITY OF ALTERNARIA BLIGHT OF PIGEONPEA IN EASTERN PART OF UTTAR PRADESH AND ADJOINING DISTRICTS OF WESTERN BIHAR - LAXMAN PRASAD BALAI; R. B. SINGH; S. M. YADAV (The Bioscan, 2013)
A roving survey of pigeonpea crop was carried out to assess the disease intensity of alternaria blight during rabi seasons 2009-10 and 2010-11 in Azamgarh, Ballia, Bhadohi, Chandauli, Ghazipur, Jaunpur, Mau, Mirzapur, Sohanbhdra and Varanasi of Eastern Uttar Pradesh and five neighboring districts of Bihar, viz. Sivan, Buxar, Arah, Bhabhua and Aurangabad. The disease intensity in different areas varied from 16.93 to 38.59 percent and 15.12 to 38.86 percent in the aforesaid two years. The disease intensity during 2009-10 was highest at Aurangabad district (32.97-38.59%) and in the year 2010-11, maximum disease intensity was recorded at Sivan district (25.22-38.86%). The congenial weather conditions like heavy rainfall, higher relative humidity and moderate temperature might have helped in building up of high disease pressure in Aurangabad and Sivan districts